Responsibility of the perpetrators of the crime of drug abuse category I for themselves (Study Decision Number: 103/Pid.Sus/2023/PN Kot) - Utami, Andora Febi; Jainah, Zainab Ompu (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The problem of narcotics abuse in Indonesia is currently very worrying. This is due, among other things, to Indonesia being located between two continents and considering the development of science and technology, the influence of globalization and very advanced transportation and a shift in materialistic values with the dynamics of the target market for illicit trafficking. Narcotics are drugs or substances that are useful in the fields of medicine, health services and scientific development. However, on the other hand, it can cause dependency which is very detrimental if it is used without control and supervision by certain individuals. Then, to make it easier to pronounce it, it can be abbreviated to the term Narcotics, namely Narcotics and dangerous addictive drugs. The problem in this research is what are the factors that cause perpetrators to abuse class I narcotics for themselves and how accountable perpetrators of class I narcotics abuse are for themselves based on Decision Number: 103/Pid.Sus/PN Kot. The research method used in this research is a normative juridical approach and an empirical approach. This normative approach is carried out by viewing legal issues as rules that are considered appropriate to normative juridical research. Normative juridical research is carried out by means of literature studies on matters of a theoretical nature, namely an approach carried out by examining legal sources, legal principles and opinions of scholars as well as applicable laws and regulations. The Empirical Approach is an approach carried out through direct research on the research object by means of observation and interviews related to the research problem. The results of this research show that the factors that cause perpetrators to abuse class I narcotics for themselves are based on internal and external factors. The internal factors that exist in himself are due to problems in his family or at home where he is looking for an escape to calm himself down, while external factors occur due to the influence of bad social interactions and the curiosity of young people. Then, the responsibility of the perpetrator of the crime of narcotics abuse of class I is for himself, which can have a detrimental impact on individuals and society, especially the younger generation, and can even cause a greater danger to the life and cultural values of the nation. In this case the defendant has been detained by members of the Tanggamus Police. The prosecutor as public prosecutor imposed charges against the defendant in the form of imprisonment for 1 (one) year and 4 (four) months, which the judge then sentenced to imprisonment for 1 (one) year as stated in Decision Number 103/Pid.Sus/ 2023/PN City. The author's suggestion is for the public to be careful and more aware of narcotics abuse in their environment by taking approaches so as not to cause division and providing support to stop using narcotics and not ostracizing narcotics abusers. For the government/officials to further improve the quality of training for convicts who abuse narcotics and be more active in implementing the eradication of narcotics abusers.